Dendroclimatology of teak indicates prevailing climatic conditions of tropical moist forests in India. (October 2021) - Upadhyay, Keshav Kumar; Shah, Santosh K.; Roy, Arijit; Tripathi, Shri Kant
Highlights: Teak tree ring widths indicates prevailing climatic conditions in tropical forests. Teak tree ring widths changes act as fuction of growth to climatic variables. Soil moisture and low precipitation determine tree growth rates in tropics. Moisture stresses indicate survival risk for endemic species sensitive to drought. Study reflects management implication for biodiversity in tropical ecosystems. Abstract: Among all proxy archives, tree rings are highly promising indicator of ecological and environmental processes due to their high climatic sensitivity, better annual resolution, and large spatial coverage. Seasonal importance of soil moisture dynamics and impact of drought events on tree growth development and carbon sequestration potential in tropical moist forests was assessed using the teak tree ring width index and instrumental climate data from Aizawl, Mizoram. Present analysis suggests that soil moisture during months of the early growing season with low precipitation is crucial for determining the growth of teak trees in the Northeast region of India. Results of the present study reflected the impact of remote atmospheric climate regulation modes such as El Niño-Southern Oscillation (ENSO), Pacific Decadal Oscillation (PDO), Sea surface temperature (SST) and Southern Oscillation Index (SOI) on site climate. Results indicate that the increasing moisture stresses in the region may cause the survival risk for the other forest vegetation having low adaptability to climate change stresses with the inability to make niche shifts. Increasing the number of tree ring studies linked with eco-physiological parameters of tree growth is recommended to better visualize the level of stresses on the trees in the moist tropical forests. This information will be useful in developing better management plans for biodiversity conservation in the tropical region.